Dusky legend : biography of Sam Anderson, Aboriginal cricketer - Ryan, Maurice 1932- (Lismore, N.S.W. : Northern Rivers Press, 2001)
Story of Aboriginal cricketer Sam Anderson who at a time when racial consciousness was dominated by its political credos of segregation and non-citizenship stood as a hero for black and white alike.
Digital master available
Keywords: Anderson, Sam, -- -1959.; Cricket players, Aboriginal Australian; Cricket players -- Australia -- Biography; Waka Waka / Wakka Wakka people (E28) (Qld SG56-10); Sport - Cricket; Woodenbong (NSW N Coast SH56-02); Glencoe (Qld Far NW SF54-01); Casino (NSW N Coast SH56-03); Purga (SE Qld SG56-14); Deebing Creek (SE Qld SG56-14)